Early and intermediate age-related macular degeneration: update and clinical review - García-Layana A (Dove Medical Press, 2017)
Alfredo García-Layana,1–3 Francisco Cabrera-López,4,5 José García-Arumí,6–8 Lluís Arias-Barquet,9,10 José M Ruiz-Moreno3,11,12 1Department of Ophthalmology, Clínica Universidad de Navarra, Pamplona, Spain; 2Sociedad Española de Retina y Vítreo (SERV), Madrid, Spain; 3Red Telemática de Investigación Cooperativa Oftared, Instituto de Salud Carlos III, Madrid, Spain; 4Service of Ophthalmology, Complejo Hospitalario Universitario Insular Materno-Infantil de Gran Canaria, Las Palmas de Gran Canaria, Spain; 5Las Palmas Gran Canaria University, Las Palmas de Gran Canaria, Spain; 6Department of Retina and Vitreous, Instituto de Microcirugía Ocular (IMO), Barcelona, Spain; 7Department of Ophthalmology, Universidad Autónoma de Barcelona, Barcelona, Spain; 8Hospital Universitario Valle Hebrón, Barcelona, Spain; 9Section of Medical-Surgical Retina, Service of Ophthalmology, Hospital Universitari de Bellvitge, Barcelona, Spain; 10University of Barcelona, Barcelona, Spain; 11Universidad Castilla-La Mancha, Albacete, Spain; 12Vissum Corporación Oftalmológica, Madrid, Spain Abstract: Age-related macular degeneration (AMD) is the leading cause of irreversible central vision loss in developed countries. With the aging of population, AMD will become globally an increasingly important and prevalent disease worldwide. It is a complex disease whose etiology is associated with both genetic and environmental risk factors. An extensive decline in the quality of life and progressive need of daily living assistance resulting from AMD among those most severely affected highlights the essential role of preventive strategies, particularly advising patients to quit smoking. In addition, maintaining a healthy diet, controlling other risk factors (such as hypertension, obesity, and atherosclerosis), and the use of nutritional supplements (antioxidants) are recommendable. Genetic testing may be especially important in patients with a family history of AMD. Recently, unifying criteria for the clinical classification of AMD, defining no apparent aging changes; normal aging changes; and early, intermediate, and late AMD stages, are of value in predicting AMD risk of progression and in establishing recommendations for the diagnosis, therapeutic approach, and follow-up of patients. The present review is focused on early and intermediate AMD and presents a description of the clinical characteristics and ophthalmological findings for these stages, together with algorithms for the diagnosis and management of patients, which are easily applicable in daily clinical practice. Keywords: age-related macular degeneration, early AMD, intermediate AMD, risk factors, classification, prevention, nutritional supplementation